2016
DOI: 10.14499/indonesianjpharm27iss3pp128
|View full text |Cite
|
Sign up to set email alerts
|

Monosodium Glutamate Exposure at Early Developmental Stage Increases Apoptosis and Stereotypic Behavior Risks on Zebrafish (Danio Rerio) Larvae

Abstract: Excessive glutamate may give neurotoxic effects and contribute to Autism spectrum disorder(ASD). In this study, we investigated prolonged exposure effects of 10 µg/mL Monosodium Glutamate (MSG) on intracellular calcium level, bax, bcl-2, ratio of bax/bcl-2 genes expression, caspase-3, apoptosis of brain cells and stereotypic behavior of Zebrafish (Danio rerio) larvae at early developmental stages. Genes expression were determined by real time PCR, caspase-3 using ELISA, intracellular Ca 2+ and apoptotic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…At 30 to 50 mM embryos had a lower heart rates and presented the afore mentioned deformities, but with mortality within 96 to 144 hpf; development ceased completely at 75 to 100 mM concentration. The NOEC and LC50% were recorded at 5 and 29.4 mM dose, respectively.Neurotoxicity has also been tested on flavor enhancers, such as monosodium glutamate, concluding that exposure at early embryonic stage increased brain cell damage and risk of behavior changes(Kurnianingsih et al 2016). Sweeteners such as aspartame and saccharin have been tested using the zebrafish model.…”
mentioning
confidence: 99%
“…At 30 to 50 mM embryos had a lower heart rates and presented the afore mentioned deformities, but with mortality within 96 to 144 hpf; development ceased completely at 75 to 100 mM concentration. The NOEC and LC50% were recorded at 5 and 29.4 mM dose, respectively.Neurotoxicity has also been tested on flavor enhancers, such as monosodium glutamate, concluding that exposure at early embryonic stage increased brain cell damage and risk of behavior changes(Kurnianingsih et al 2016). Sweeteners such as aspartame and saccharin have been tested using the zebrafish model.…”
mentioning
confidence: 99%
“…Histopathological study of the brain of zebrafish from 10 ppm, 100 ppm, and 1000 ppm MSG group have showed no lesions different from the control group. In contrast, from the previous study found that MSG can cause apoptosis of brain cells of zebrafish larvae (Kurnianingsih et al, 2016) and increased cell hypertrophy and tissue edema in the region of the nucleus lateralis tuberis near pituitary gland area after 24-hours post injected MSG into the adult goldfish brain (Peter et al, 1980).…”
Section: Other Resultsmentioning
confidence: 64%
“…The median lethal concentration (LC50) of zebrafish embryo at 48 hpf is 1.525%w/v and at 96 hpf is 1.039%w/v (Ponpornpisit and Suthamnatpong, 2016). The neuronal effect of MSG was induced brain cell apoptosis at 1-day postfertilization of zebrafish embryo exposed to 10 µg/mL MSG for 24 -72 hours which was associated with behavioral changes in decreased locomotor activities (Kurnianingsih et al, 2016).…”
Section: Introduction Importance and Rationalementioning
confidence: 99%